Reduction-free ethanol dehydrogenation catalyst as well as preparation method and application thereof
By adding mannitol and Li elements to the ethanol dehydrogenation catalyst, the problem of catalyst reduction is solved, the stability of the catalyst and the selectivity of acetaldehyde are improved, and the effect of efficient catalyzing of ethanol dehydrogenation reaction without reduction is achieved.
Patent Information
- Application Number
- CN202411489142.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing ethanol dehydrogenation catalysts need to be reduced to be used normally, and are prone to inactivate due to the migration and agglomeration of copper particles, affecting the selectivity and stability of the reaction.
Using Cu-Li/SiO2 catalyst, mannitol and a small amount of Li elements are added to the catalyst, and mannitol is used to separate CO during the roasting process to achieve the reduction of copper species on the surface of the catalyst, and the content of by-products is reduced by Li elements to improve the selectivity of acetaldehyde.
A high activity and high stability ethanol dehydrogenation catalyst is achieved without reduction, which improves the selectivity of acetaldehyde and reduces the generation of by-products.
Smart Images

Figure CN119680553A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to an ethanol dehydrogenation catalyst that does not require reduction, and a preparation method and application thereof. Background Art
[0002] In recent years, the effective utilization of bioethanol as a renewable resource has attracted people's attention, and the sustainable route of directly preparing acetaldehyde by dehydrogenation under the action of catalyst has become one of the research hotspots. Ethanol can be selectively dehydrogenated to produce acetaldehyde, and then acetaldehyde is used as a raw material to synthesize high-value-added chemicals such as butanol, 1,3-butadiene and 1,3-propylene glycol. This process route is a rich and expansion of the technical route of syngas to downstream chemical products.
[0003] At present, Cu / SiO2 catalyst is often used in the direct dehydrogenation of ethanol to prepare acetaldehyde. However, since the theoretical surface lattice migration temperature and sintering temperature of Cu are 134°C and 405°C respectively, it is easy to migrate, agglomerate or even sinter during the reaction. Therefore, the Cu / SiO2 catalyst is easily deactivated due to aggregation and sintering. Secondly, since the abundant silanol (Si-OH) on the surface of the silicon oxide carrier can catalyze the secondary reactions such as aldol condensation of the target product acetaldehyde, or catalyze the dehydration of ethanol to produce ethylene or ether, the selectivity of acetaldehyde is reduced. Therefore, in order to obtain a highly selective and highly stable dehydrogenation catalyst, the preparation method of the catalyst and the addition of an auxiliary agent are often the hot spots of research. Patent CN114054079A and Patent CN114054079A respectively publicly reported different catalyst preparation methods, and applied them to the ethanol dehydrogenation reaction to obtain good dehydrogenation activity and stability. However, the obtained catalysts need to be reduced before they can be used normally. In order to improve the selectivity of acetaldehyde, Zhang Yue doped alkali metals into the Cu / SiO2 catalyst to improve the selectivity of acetaldehyde. However, when the amount of alkali metal added is small, the effect is not obvious. When the amount added is large, the active sites will be covered, reducing the utilization rate and reaction activity of metal Cu. Summary of the invention
[0004] The purpose of the present invention is to provide an ethanol dehydrogenation catalyst that does not require reduction, and a preparation method and application thereof, so as to solve the technical problem that catalysts in the prior art must be reduced before they can be used normally.
[0005] The invention discloses an ethanol dehydrogenation catalyst which does not require reduction. The catalyst is a Cu-Li / SiO2 catalyst, wherein Cu is an active component, mannitol is a dopant, and Li is a modifier.
[0006] Furthermore, the content of the active component Cu element in the catalyst is 2.0wt%-25wt%, the molar ratio of the dopant mannitol to Cu is 0.01-0.1, the content of the modifier Li element in the catalyst is 0.01wt%-0.1wt%, and the rest is the carrier.
[0007] Furthermore, the carrier is silicon dioxide.
[0008] A method for preparing an ethanol dehydrogenation catalyst that does not require reduction comprises the following steps:
[0009] Step 1, adding dopant mannitol into a soluble salt solution of Cu and stirring evenly;
[0010] Step 2, adding an aqueous ammonia solution to the solution of step 1 to obtain a first solution;
[0011] Step 3, mixing the first solution obtained in step 2 with the silica sol solution, stirring, heating to evaporate ammonia, then filtering, washing, and drying to obtain a Cu / SiO2 sample containing a dopant;
[0012] Step 4: impregnate the Cu / SiO2 sample with a soluble salt solution of Li, and then dry it to obtain a Cu-Li / SiO2 catalyst.
[0013] The addition of mannitol is one of the key technologies of the present invention. Mannitol is used as a doping agent. During the calcination process of the doped catalyst, mannitol will decompose and release reducing gas CO, thereby directly reducing the copper species on the catalyst surface. Secondly, during the catalyst preparation process, part of the copper ions will coordinate with the mannitol molecules, and mannitol will also wrap part of the copper ions and silicon dioxide. When the catalyst containing mannitol is calcined in a N2 atmosphere, Cu2O and Cu 0 and CuO species, of which Cu2O can not only provide Cu + , and can effectively inhibit the migration and agglomeration of copper nanoparticles, thereby further improving the stability of the ethanol dehydrogenation catalyst.
[0014] The addition of Li element is another key technology of the present invention. In the research process of the present invention, the content of by-products in the dehydrogenation product can be reduced by adding a small amount of Li element to the Cu / SiO2 sample, thereby improving the selectivity of acetaldehyde. Li is a modifying element of the catalyst of the present invention.
[0015] Furthermore, the soluble Cu salt is at least one of Cu(NO3)2 and its hydrate; the soluble Li salt is at least one of LiNO3 and its hydrate.
[0016] Furthermore, the mass concentration of the ammonia aqueous solution is 10wt%-25wt%, and the molar ratio of ammonia to Cu is greater than 4.
[0017] Furthermore, in the step 1, the stirring time is 0.5h-12h; in the step 3, the temperature of ammonia evaporation is 60°C-95°C, the pH value of the solution after ammonia evaporation is between 5-7, the drying temperature is 50°C-130°C, and the drying time is 4h-48h.
[0018] Furthermore, in step 4, the drying temperature is 50° C.-130° C., and the drying time is 4 h-48 h.
[0019] The invention discloses an application of an ethanol dehydrogenation catalyst which does not require reduction, and is used for catalyzing the dehydrogenation of ethanol to prepare acetaldehyde.
[0020] Further, using a fixed bed reactor, the application method comprises the following steps:
[0021] Step 1, filling the Cu-Li / SiO2 catalyst in a fixed bed, and heat treating it with pure nitrogen at a temperature of 250°C to 500°C for a treatment time of 4h to 24h;
[0022] Step 2: After the heat treatment, the temperature is lowered to the reaction temperature, and the nitrogen flow rate is adjusted to pump in the ethanol solution for reaction.
[0023] Furthermore, the mass space velocity of ethanol in step 2 is 0.1h -1 -4h -1 ; The nitrogen volume space velocity is 2000h -1 -12000h -1 .
[0024] Furthermore, in step 2, the reaction pressure is normal pressure-1.0 MPa, and the reaction temperature is 200°C-300°C.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The catalyst preparation process of the present invention is simple, and only a small amount of mannitol is used for doping, so that the catalyst is used in the reaction of ethanol dehydrogenation to acetaldehyde, and the catalyst does not need a hydrogen reduction step, and a high-activity and high-stability dehydrogenation catalyst can be directly obtained. At the same time, only a small amount of Li element is added to reduce the content of ethylene and ether in the dehydrogenation product, and improve the selectivity of the product acetaldehyde. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only represent some embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0028] Figure 1 This is a catalyst activity data diagram of the long-term operation of Catalyst A according to an embodiment of the present invention.
[0029] Figure 2 This is a catalyst activity data diagram of comparative catalyst E during long-term operation. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments.
[0031] Example 1
[0032] The ethanol dehydrogenation catalyst without reduction of the above device used in this embodiment comprises the following steps:
[0033] Take 5.71g Cu(NO3)2·3H2O and 0.17g mannitol [mannitol: Cu=0.04] and dissolve them in 200mL deionized water, add 18.18g concentrated ammonia water with a concentration of 25%-28% to form a complex, and obtain a dark blue solution. At room temperature, add 93.74g silica sol solution (silicon content 30%) to the above solution, stir for 1h, heat to 90℃ to evaporate ammonia until the pH value of the solution drops to between 6-7, stop evaporating ammonia, filter, wash with hot water three times, and dry the sample in an oven at 110℃ for 24h to obtain a Cu / SiO2 sample containing a dopant.
[0034] Take 0.15g LiNO3 and dissolve it in 50mL deionized water, then add the Cu / SiO2 sample into the solution, stir evenly and soak for 4h, then dry in an oven at 110℃ for 24h, Cu-Li / SiO2 catalyst A, in which the Cu content is 5.0wt% and the Li content is 0.05wt%.
[0035] Example 2
[0036] Take 11.41g Cu(NO3)2·3H2O and 0.34g mannitol [mannitol: Cu=0.04] and dissolve them in 200mL deionized water, add 36.37g concentrated ammonia water with a concentration of 25%-28% to form a complex, and obtain a dark blue solution. At room temperature, add 87.47g silica sol solution (silicon content 30%) to the above solution, stir for 1h, heat to 90℃ to evaporate ammonia until the pH value of the solution drops to between 6-7, stop evaporating ammonia, filter, wash with hot water three times, and dry the sample in an oven at 110℃ for 24h to obtain a Cu / SiO2 sample containing a dopant.
[0037] Take 0.15g LiNO3 and dissolve it in 50ml deionized water, then add the Cu / SiO2 sample into the solution, stir evenly and soak for 4h, then dry in an oven at 110℃ for 24h, Cu-Li / SiO2 catalyst B, in which the Cu content is 10.0wt% and the Li content is 0.05wt%.
[0038] Example 3
[0039] Take 5.71g Cu(NO3)2·3H2O and 0.34g mannitol [mannitol: Cu=0.08] and dissolve them in 200mL deionized water, add 18.18g concentrated ammonia water with a concentration of 25%-28% to form a complex, and obtain a dark blue solution. At room temperature, add 93.74g silica sol solution (silicon content 30%) to the above solution, stir for 1h, heat to 90℃ to evaporate ammonia until the pH value of the solution drops to between 6-7, stop evaporating ammonia, filter, wash with hot water three times, and dry the sample in an oven at 110℃ for 24h to obtain a Cu / SiO2 sample containing a dopant.
[0040] Take 0.15g LiNO3 and dissolve it in 50mL deionized water, then add the Cu / SiO2 sample into the solution, stir evenly and soak for 4h, then dry in an oven at 110℃ for 24h, Cu-Li / SiO2 catalyst C, in which the Cu content is 5.0wt% and the Li content is 0.05wt%.
[0041] Example 4
[0042] Take 5.71g Cu(NO3)2·3H2O and 0.17g mannitol [mannitol: Cu=0.08] and dissolve them in 200mL deionized water, add 18.18g concentrated ammonia water with a concentration of 25%-28% to form a complex, and obtain a dark blue solution. At room temperature, add 93.74g silica sol solution (silicon content 30%) to the above solution, stir for 1h, heat to 90℃ to evaporate ammonia until the pH value of the solution drops to between 6-7, stop evaporating ammonia, filter, wash with hot water three times, and dry the sample in an oven at 110℃ for 24h to obtain a Cu / SiO2 sample containing a dopant.
[0043] Take 0.30g LiNO3 and dissolve it in 50mL deionized water, then add the Cu / SiO2 sample into the solution, stir evenly and soak for 4h, then dry in an oven at 110℃ for 24h, Cu-Li / SiO2 catalyst D, in which the Cu content is 5.0wt% and the Li content is 0.10wt%.
[0044] Comparative Example 1
[0045] Take 5.71g Cu(NO3)2·3H2O and dissolve it in 200mL deionized water, add 18.18g concentrated ammonia water with a concentration of 25%-28% to form a complex, and obtain a dark blue solution. At room temperature, add 93.74g silica sol solution (silicon content 30%) to the above solution, stir for 1h, heat to 90℃ to evaporate ammonia until the pH value of the solution drops to between 6-7, stop evaporating ammonia, filter, wash with hot water three times, dry the sample in an oven at 110℃ for 24h, and calcine in a muffle furnace at 400℃ for 4h to obtain Cu / SiO2 catalyst E, in which the Cu content is 5wt%.
[0046] Comparative Example 2
[0047] Take 5.71g Cu(NO3)2·3H2O and 0.17g mannitol [mannitol: Cu=0.04] and dissolve them in 200mL deionized water, add 18.18g concentrated ammonia water with a concentration of 25%-28% to form a complex, and obtain a dark blue solution. At room temperature, add 93.74g silica sol solution (silicon content 30%) to the above solution, stir for 1h, heat to 90℃ to evaporate ammonia until the pH value of the solution drops to between 6-7, stop evaporating ammonia, filter, wash with hot water three times, and dry the sample in an oven at 110℃ for 24h to obtain a dopant-containing Cu / SiO2 catalyst F, in which the Cu content is 5.0wt%.
[0048] Comparative Example 3
[0049] Take 5.71g Cu(NO3)2·3H2O and 0.17g mannitol [mannitol: Cu=0.04] and dissolve them in 200mL deionized water, add 18.18g concentrated ammonia water with a concentration of 25%-28% to form a complex, and obtain a dark blue solution. At room temperature, add 93.74g silica sol solution (silicon content 30%) to the above solution, stir for 1h, heat to 90℃ to evaporate ammonia until the pH value of the solution drops to between 6-7, stop evaporating ammonia, filter, wash with hot water three times, and dry the sample in an oven at 110℃ for 24h to obtain a Cu / SiO2 sample containing a dopant.
[0050] Take 0.74g LiNO3 and dissolve it in 50mL deionized water, then add the Cu / SiO2 sample into the solution, stir evenly and soak for 4h, then dry in an oven at 110℃ for 24h, Cu-Li / SiO2 catalyst G, in which the Cu content is 5.0wt% and the Li content is 0.25wt%.
[0051] The prepared catalyst AG was used in the experiment of ethanol dehydrogenation to acetaldehyde. The activity of the catalyst was evaluated using a fixed-bed continuous flow reactor. The inner diameter of the reaction tube was 1.2 cm, and 5 mL of catalyst was loaded. Quartz sand was loaded at the upper and lower ends of the catalyst for uniform distribution of the gas. Before the reaction, the catalyst was programmed to heat up at a rate of 1°C / min to 450°C and calcined for 4 hours under a N2 atmosphere. After the calcination, the temperature was lowered to the reaction temperature, the N2 flow rate was adjusted, and the liquid raw material 95% aqueous ethanol was injected into the reactor at a certain flow rate. The reaction pressure was 1.0 MPa, the reaction temperature was 220°C, and the gas space velocity was 9500h -1 , liquid hourly space velocity is 2.4h -1 The dehydrogenation reaction was carried out under the conditions of , and after the system was stable, samples were taken for quantitative analysis by chromatography to calculate the dehydrogenation activity of the catalyst.
[0052] The performance test results of the embodiments are listed in Table 1. In addition, the stability test of the dehydrogenation of some catalysts to produce acetaldehyde is shown in the attached Figure 1 and 2 shown.
[0053] Table 1 Catalyst activity test results of the examples
[0054] catalyst Ethanol conversion rate % Acetaldehyde selectivity % Ethylene selectivity % A 30.16% 94.33% 0.04% B 35.14% 93.03% 0.07% C 30.95% 93.75% 0.06% D 30.25% 93.76% 0.05% E 3.18% - - F 29.94% 91.33% 0.62% G 25.56% 93.41% 0.05%
[0055] It can be seen from the experimental results in Table 1 that the catalysts AD prepared by the present invention have a good ethanol conversion rate and a high acetaldehyde selectivity without reduction, and the selectivity of the byproduct ethylene is very low, less than 0.1%. Compared with the catalysts obtained by the conventional preparation method (such as comparative catalyst E), the catalysts obtained by the present invention have better stability (such as Figure 1 ); while for comparison catalyst E, without adding mannitol and without reduction, the catalyst had almost no activity (Table 1). After reduction, comparison catalyst E was tested for a long period of time, and the catalyst stability began to gradually deactivate after 350h ( Figure 2 ); Compared with catalyst F, without adding Li, the catalyst has certain activity, but the selectivity of byproduct ethylene is obviously higher. Compared with catalyst G, with adding a large amount of Li, the catalyst has good selectivity, but the conversion rate of ethanol is significantly reduced.
[0056] The above are the implementation methods listed in this embodiment, but this embodiment is not limited to the above optional implementation methods. Those skilled in the art can arbitrarily combine the above methods to obtain other various implementation methods. Anyone can derive other various forms of implementation methods under the inspiration of this embodiment. The above specific implementation methods should not be understood as limiting the scope of protection of this embodiment. The scope of protection of this embodiment shall be based on the definition in the claims, and the description can be used to interpret the claims.
Claims
1. An ethanol dehydrogenation catalyst that does not require reduction, characterized in that: The catalyst is a Cu-Li / SiO2 catalyst, wherein Cu is an active component, mannitol is a dopant, and Li is a modifier.
2. The ethanol dehydrogenation catalyst that does not require reduction according to claim 1, characterized in that: The content of the active component Cu element in the catalyst is 2.0wt%-25wt%, the molar ratio of the dopant mannitol to Cu is 0.01-0.1, the content of the modifier Li element in the catalyst is 0.01wt%-0.1wt%, and the rest is the carrier.
3. The ethanol dehydrogenation catalyst that does not require reduction according to claim 2, characterized in that: The carrier is silicon dioxide.
4. A method for preparing an ethanol dehydrogenation catalyst that does not require reduction, characterized in that: The following steps are involved: Step 1, adding dopant mannitol into a soluble salt solution of Cu and stirring evenly; Step 2, adding an aqueous ammonia solution to the solution of step 1 to obtain a first solution; Step 3, mixing the first solution obtained in step 2 with the silica sol solution, stirring, heating to evaporate ammonia, then filtering, washing, and drying to obtain a Cu / SiO2 sample containing a dopant; Step 4: impregnate the Cu / SiO2 sample with a soluble salt solution of Li, and then dry it to obtain a Cu-Li / SiO2 catalyst.
5. The method for preparing an ethanol dehydrogenation catalyst that does not require reduction according to claim 4, characterized in that: The soluble Cu salt is at least one of Cu(NO3)2 and its hydrate; the soluble Li salt is at least one of LiNO3 and its hydrate.
6. The method for preparing an ethanol dehydrogenation catalyst that does not require reduction according to claim 4, characterized in that: The mass concentration of the ammonia solution is 10wt%-25wt%, and the molar ratio of ammonia to Cu is greater than 4.
7. The method for preparing an ethanol dehydrogenation catalyst that does not require reduction according to claim 4, characterized in that: In the step 1, the stirring time is 0.5h-12h; in the step 3, the temperature of ammonia evaporation is 60°C-95°C, the pH value of the solution after ammonia evaporation is between 5-7, the drying temperature is 50°C-130°C, and the drying time is 4h-48h.
8. The method for preparing an ethanol dehydrogenation catalyst that does not require reduction according to claim 4, characterized in that: In the step 4, the drying temperature is 50° C.-130° C., and the drying time is 4 h-48 h.
9. An application of an ethanol dehydrogenation catalyst that does not require reduction, characterized in that: A catalyst prepared by using the method for preparing an ethanol dehydrogenation catalyst that does not require reduction as described in any one of claims 1 to 3 or an ethanol dehydrogenation catalyst that does not require reduction as described in any one of claims 4 to 8 is used for catalyzing the dehydrogenation of ethanol to prepare acetaldehyde.
10. The use of an ethanol dehydrogenation catalyst that does not require reduction according to claim 9, characterized in that: Using a fixed bed reactor, the application method comprises the following steps: Step 1, filling the Cu-Li / SiO2 catalyst in a fixed bed, and heat treating it with pure nitrogen at a temperature of 250°C to 500°C for a treatment time of 4h to 24h; Step 2: After the heat treatment, the temperature is lowered to the reaction temperature, and the nitrogen flow rate is adjusted to pump in the ethanol solution for reaction.
Citation Information
Patent Citations
Preparation method and application of catalyst for preparing acetaldehyde through ethanol dehydrogenation
CN114054079A